Mercury removal petrochemical wastewater using hollow fiber external membrane bioreactor - Khairul Bahrin, Shafie (2009)
Nowadays, mercury removal from Petrochemical waste by using external membrane bioreactor is becoming one of the favourite biological treatments used to preserve the environment. This treatment is conducted by using Pseudomonas putida as the biological sources to reduce the mercury content in the waste. Combination membrane system with bioreactor after treatment process is to remove mercury effectively The purpose hollow fiber membrane to filter out any supernatant like suspended solid, turbidity and mercury concentration that polluted the water sources Mercury removals in this study are in aerobic phase. The objective of the present study was to investigate the influence of aeration rate and agitation speed using Pseudomonas putida. The mercury removal process was conducted under various aeration rates is 0.5, 1.0 and 1.5 L/min and agitation speeds 100, 180 and 200 rpm respectively in external membrane bioreactor. The optimum temperature for growth of bacteria is 37°C and pH is 6-7. Parameter studied in this experiment work is agitation speed and aeration rate. Dependencies of this parameter to the growth of the bacteria are studied. The optimum aeration rate for this study is 1.0 L/min and agitation speed is 180 rpm. The other parameters significant study is total suspended solid(TSS), biological oxygen demand(BOD), chemical oxygen demand (COD) and turbidity. This parameter also to meet the requirement of Malaysia DOE, Standard (B) on Environmental Quality Act 1974. This study can be concluded that successful mercury can be conducted using Pseudomonas putida The scale up of bioreactor could be done for massive mercury removal from petrochemical has.